PERLINDUNGAN HUKUM TERHADAP PEREMPUAN PADA TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA - Zahra, Laila; Sinaga, Niru Anita; Sudarto, Sudarto (Neolectura, 2024)
Interviewing the respondents or informants. The method in this research is juridical empiric method. The result of this research shows that the legal regulation which influence the law enforcement towards Domestic Violence within the household is the Law No. 23 of 2004 on the eradication of Domestic Violence within the household. However, if before entering the litigation way, it is mediated in advance with the rule of Gampong and if a marriage is not recognized by the state so that the domestic violence is subjected to Article 351 of the Criminal Code. The law enforcer that influences the law enforcement against domestic violence within the household except the police, prosecutor, and court is (KPPPA). This institution also has an active role and is also involved to handle the domestic violence cases. Visumetrepertumis most important form of infrastructure and facilities and also becomes evidence in domestic violence cases. The societies who tend to be victims of domestic violence are women. The culture that influences law enforcement against domestic violence is patriarchal culture which strongly dominates in the household of the societies in Indonesia. As the Suggestion, in order to reach the realization of the effectiveness of law enforcement for domestic violence within the household so that the influenced factors should be better, especially for the State apparatus. They should conduct their duties properly.